Recovery of Crocins From Floral Tissue of Gardenia jasminoides Ellis - Sommano, Sarana Rose; Suppakittpaisarn, Pongsakorn; Sringarm, Korawan; Junmahasathien, Taepin; Ruksiriwanich, Warintorn (Frontiers in Nutrition, 2020)
In this research, novel source of phytopigment crocins from fully-open mature flower of cape jasmine (Gardenia jasminoides) was introduced. Methanol and DIH2O were appropriate for pigment recovery with the maximum yields of at least 17% from the floral tissue. Pigment separation by Thin Layer Chromatography also confirmed the presence of the carotenoids, which well dissolved in these high strength polar solvents in fruit, flower, as well as leaf materials. The spectra patterns of the extracts from Ultraviolet and Nuclear Magnetic Resonance showed the maximum absorption at ~420 nm and the chemical shift values that were similar to those of crocetin aglycones (crocins) in the methanol extracts of the commercial source of gardenia yellow (fructus or fruit of G. florida). Chemical compositions were then evaluated using an aqueous phase-Capillary Electrophoresis of the methanol extracts. The methanolic extracts of the flower and fruit had 11 principal ingredients in common. Among those, crocetin and crocins 2 were of the crocin group known as major components of commercial gardenia yellow. The research outcome not only urges the sustainable way of raw material utilisation for natural product recovery, but also encourage the movement toward edible landscape for the community.